Notes on the genus Allotrichosiphum (Hemiptera: Aphididae: Greenideinae), with the description of one new species from Hong Kong, China - Qiao, Gexia; Jiang, Liyun; Martin, Jon H. (Zootaxa, 2006)
The aphid genus Allotrichosiphum is reviewed here. Allotrichosiphum cyclobalanopsidis sp. nov. from Cyclobalanopsis neglecta in Hong Kong, China is described. Keys to the species of Allotrichosiphum worldwide are provided. The type specimens studied are deposited in the Natural History Museum, London, U.K.